Analysis of the Causes of People Not Choosing Islamic Banks: Research on Gabuswetan Village Communities, Indramayu Regency - Irwan Maulana (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2022)
This paper aims to answer questions about how people perceive Islamic banks and what factors cause people not to choose Islamic banks. The research data was collected from direct interviews with the people in Gabuswetan Village, Indramayu Regency. Interviews were conducted with people who did not choose Islamic banks as their financial institutions. Furthermore, this study was analyzed using a qualitative descriptive analysis method. The results of the study show that people who do not choose Islamic banks think that Islamic banks are the same as conventional banks. This is due to the low level of public knowledge considering the lack of promotion by Islamic banks. The public still feels that the information that reaches them about Islamic banking, starting from the system, concept to the product, is very little. Factors that cause people not to choose Islamic banks include knowledge of Islamic banks, products and their very low existence. In addition, there are very few Islamic bank service offices and ATMs around the community. Apart from that, Islamic bank branding is felt to be lacking because of the minimal events and promos carried out by Islamic banks. Seeing the state of society like that, Islamic banks should provide education to the public about Islamic banks, starting from the system to its products. Islamic banks are expected to provide educational promotions by getting closer to the community directly. In addition, the fulfillment of facilities that support services to customers is also needed in order to provide the best service to the public.